IPCC and GGA expert group (GGA Expert Group on Food, Water & Health and the Food systems-related adaptation and mitigation in the AR7 IPCC cycle) - CGIAR (CGIAR, 2024)
IPCC and GGA expert group (GGA Expert Group on Food, Water & Health and the Food systems-related adaptation and mitigation in the AR7 IPCC cycle)